Female assignment to care in times of pandemic: guilt and rituals of life and death - Jiménez Argüello, Brenda (2022)
This work investigates the impact that the pandemic situation in Costa Rica has had on women. A bibliographical study was carried out to consider conceptual contributions of gender theory that allowed to cover categories capable of showing how the allocation of care continues to be in the hands of women and this has affected their physical and emotional health. This assignment is reproduced through a patriarchal culture with Catholic features that justifies beliefs, roles and violent actions towards women, as well as through the incidence that religion has in our Costa Rican context. In addition, the pandemic situation led to a break with rituals of life and death, having consequences in society.